The Home Literacy Environment in Rural Rwanda and Its Relationship to Early Grade Reading. (3rd March 2020) - Friedlander, Elliott W.
ABSTRACT: The developing world faces a learning crisis, wherein children fail to master basic skills despite years of primary school attendance. The literature indicates that both in-school and at-home experiences impact children's reading development, yet most developing world studies focus on children's in-school experiences exclusively. This current study addresses this imbalance by exploring the home literacy environment in rural Rwanda and its relationship to children's reading development. The data come from 466 parent surveys and 466 child reading assessments. An exploratory factor analysis of the survey data yields 5 distinct factors of the home literacy environment: family literacy and learning at home, parental competency in literacy, reading materials, child interest in literacy, and religious-related reading activities. Multivariate regression analyses reveal that family learning, parent competency, and child interest significantly predict early grade reading achievement. Implications of these findings for the developing world's learning crisis are discussed.